NOVEL LAYLA KARYA CANDRA MALIK: KAJIAN PSIKOLOGI SASTRA DAN NILAI RELIGIUS - Sanditama, Edwin; Waluyo, Herman J.; Suwandi, Sarwiji (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The research aims to describe. (1) the behavior of the main characters in terms of B.F Skinner's psychoanalytic theory, and (2) the religious values contained in the novel Layla by Candra Malik. This study was analyzed using a psychology literature approach. The data sources in this study are documents, namely the Layla novel by Candra Malik and informants, namely the results of interviews with Candra Malik. The sampling technique uses purposive sampling. The technique of collecting data uses the technique of reading and recording. Validity test uses theory and source triangulation. The technical analysis of the data used is flow analysis of analysis which includes data reduction, data presentation, and drawing conclusions. The results of this study are as follows: (1) the behavior of the main character in this novel responds to the stimulus given by the supporting character, which is a positive response in the form of pleasure, admiration, respect and love, while the negative response is anger, disappointment, sadness, and despair. (2) Religious values contained in the novel include five aspects, namely dimensions of belief, worship, appreciation, knowledge, and practice.